The healing of memories : African Christian responses to politically induced trauma - Girma, Mohammed (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2018)
This volume is a comprehensive and balanced examination of the African Christian response to political conflicts. Its strength lies on its focus on the healing of memories from theological, philosophical, cultural and scientific points of view.